Gwanghyun D. Choi. Decoding Canaanite Pottery Paintings from the Late Bronze Age and Iron Age I: Classification and Analysis of Decorative Motifs and Design Structures-Statistics, Distribution Patterns—Cultural and Socio- Political Implications. Orbis Biblicus et Orientalis, Series Archaeologica 37. Fribourg and Göttingen, Academic Press and Vandenhoeck & Ruprecht, 2016. 290 + CD-ROM. ISBN: 978-3-525-53039-9 - Yasur-Landau Assaf (2018)
Fil: Yasur-Landau, Assaf. University of Haifa; Israel